ANALISIS RENDAHNYA LITERASI MEMBACA SISWA KELAS 3 SEKOLAH DASAR - Saffanah Sholihah; Indah Wardatussa’idah; Chrisnaji Banidra Yudha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy is a very important activity to be implemented at an early age, especially in the scope of education, with literacy at the elementary school level being able to improve reading skills. This study analyzes the low literacy of reading books in grade 3 students which includes a discussion of the causes and factors that influence their literacy development. The ability to read, write and count students is closely related to the world of reading skills. The reading interest of students in grade 3 is still relatively low and can have a negative impact on the world of education. This study was conducted at SDN Mekarjaya 20, Depok City with the type of research used by researchers, namely Qualitative Research using a Descriptive approach, data collection techniques through observation, interviews, and documentation. The purpose of this study is to analyze the basic literacy problems faced by grade 3 students and identify solutions to improve students' literacy skills. From this study, several facts can be obtained, namely low interest in literacy, limited reading books, and lack of support from families, especially parents, while studying at home. The solution to overcome problems related to low literacy in reading books is to involve the active role and support of families, especially parents, while studying at hom.